Phenotypic and genetic parameters for growth traits in Red Chittagong Cattle of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
The present study was carried out to estimate phenotypic and genetic parameters of Red Chittagong Cattle (RCC) for growth traits. Means of birth weight (BW), three month weight (3MW), six month weight (6MW), weaning weight (WW), nine month weight (9MW) and yearling weight (YW) were 15.74, 31.48, 45.33, 57.00, 60.91 and 76.18 kg respectively. Sex significantly (p0.05) 3MW, 6MW, WW, 9MW and YW. BW, 6MW, WW, 9MW and YW did not vary significantly (p>0.05) on year of birth but varied significantly (p